Encuentros de dos mundos: contactos lingüísticos entre andinos y amazónicos en el siglo XIX - Huamán Águila, Óscar (2020)
This paper will address the linguistic contact of the Quechua language with some Arawak languages of the eastern slope of Ayacucho during the period of the 19th century. In the diaries of travelers who made their way to the foothills, it is shown that there are Amazonian inhabitants who speak the Quechua language, and from the same way, it was shown that the Quechua speakers have mastered some of the Amazonian languages. This linguistic and cultural phenomenon is shown in the texts of Antonio Raimondi (1866), José B. Samanez Ocampo (1884), Pedro Portillo (1890). This fact is due to the linguistic contact of both cultures that took place at the borders for many years before the Spanish and traveler's interference. The research topic will be approached from a Sociolinguistic approach. And from a methodology of revision of written sources and analysis.